Explaining the concept of maternal health information verification and assessment during pregnancy: a qualitative study - Safoura Taheri; Mahmoud Tavousi; Zohre Momenimovahed; Ashraf Direkvand-Moghadam; Nazanin Rezaei; Nasibeh Sharifi; Ziba Taghizadeh (BMC, 2021)
Abstract Background Pregnant women use information sources for their own health and health of their children. However, despite the importance of trusting the information sources, pregnant women may not have the ability to verify the maternal health information, which could have negative consequences for their health. The purpose of this study was to explain the concept of maternal health information verification and assessment in pregnant women according to their experiences and perception. Methods This is a qualitative study that was conducted in 2017 in Tehran, Iran. The participants in this study consisted of 19 pregnant women who were selected by purposeful sampling. To collect data, semi-structured, in-depth and face to face interviews were conducted with participants and continued until saturation of data. Conventional content analysis method was used to analyze the data and to identify concepts and synthesize them into general classes. MAXQDA software version 10 was used to manage the data. Results In the process of data analysis, the concept of verification and assessment of maternal health information in pregnancy was explained in two main categories, including "Validity of information resources" and "Reliance on information resources." The category of Validity of information resources had two subcategories of valid and invalid sources, and the main category of Reliance on information resources had two subcategories of indicators of assurance, and confusion and trying to obtain assurance. Conclusion The results indicated that pregnant women used various sources and indicators, as well as different evaluation methods to obtain information and verify it, especially when they are confused. Thus, health authorities and healthcare professionals should provide appropriate programs to familiarize mothers with credible sources, train pregnant women on standards and practices for judging the accuracy of information, and create a safe margin of information.